The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1016/j.geoforum.2014.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Morality, mobility and citizenship: Legitimising mobile subjectivities in a contested outdoors

Abstract: 1 Morality, mobility and citizenship: legitimising mobile subjectivities in a contested outdoors AbstractIn this article, we examine articulations of mobile citizenship produced through the discursive practices of state agencies, drawing in particular on a study of the contested reconfiguration of outdoor citizenship in Norway. Whilst increased participation and diversity in outdoor activities is highly valued and encouraged because of its social benefits, moral landscapes of the outdoors may be part of settli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“… Flemsæter et al, 2015 ). Notably, Flemsæter et al (2015) addressed the construction of mobile subjectivities in contested outdoor spaces in terms of “how social identities interact with the citizen responsibilities assigned to different forms of mobility, such as mountain biking, skiing and walking” (p. 342). Similarly, we examine how mobile persons become immoral in the wake of COVID-19 contact tracing.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“… Flemsæter et al, 2015 ). Notably, Flemsæter et al (2015) addressed the construction of mobile subjectivities in contested outdoor spaces in terms of “how social identities interact with the citizen responsibilities assigned to different forms of mobility, such as mountain biking, skiing and walking” (p. 342). Similarly, we examine how mobile persons become immoral in the wake of COVID-19 contact tracing.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…Technology and walking in the countryside are typically counterposed in Western societies, with computer technologies associated with increasingly sedentary cultures of work and recreation (Jarkievich et al, 2008;Lorimer, 2011), or more broadly associated with modernity and the distancing of people from the natural environment (Smith & Dunkley, 2018) and one another (Turkle, 2011). Indeed, the absence of contemporary technologies and signs of them (such as phone signal) engenders "rural skill" (Flemsaeter et al, 2015;Hunt, 2016). The characterisation of places as wild, natural, and untouched presupposes the absence or intrusiveness of screens and digital networked technologies (Brown, 2015;Lorimer & Ingold, 2005).…”
Section: Technologies Walking and Navigatingmentioning
confidence: 99%
“…Researchers have found that the uses of urban green space for recreation and sport are influenced by widely differing social and cultural values (Brown 2014;Flemsaeter, Setten, and Brown 2014;Macnaghten and Urry 1998). For example, people in western countries and of European descent tend to favour physically active forms of recreation performed in minimally managed environments such as 'first growth' urban forests that convey an image of 'authentic naturalness' (Özgüner 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Participation is indeed increasing, but it has been accompanied by new tensions. The transformation of contemporary outdoor recreation cultures based on new technologies and activities, such as modern skiing on groomed trails, snowboarding, adventure races and trail-biking, often results in discursively contested moral values, identities and practices, as well as spatial conflicts (Brown 2014;Flemsaeter, Setten, and Brown 2014). In addition, increasing urban outdoor recreation facilitation may have negative consequences, such as erosion, loss of biodiversity and fragmentation of habitats that threaten the lives of animals and plants (European Environmental Agency 2010).…”
Section: Introductionmentioning
confidence: 99%